Architecture as a Way of Seeing and Learning The built environment as an added educator in East African refugee camps - Elorduy, Nerea Amorós (Design Research in Architecture, 2021)
At the beginning of 2020, 66 long-term refugee camps existed along the East African Rift. Millions of young children have been born at the camps and have grown up there, yet it is unknown how their surrounding built environments affect their learning and development. Architecture as a Way of Seeing and Learning presents an architect's take on questions many academics and humanitarians ask. Is it relevant to look at camps through an urban lens and focus on their built environment? Which analytical benefits can architectural and design tools provide to refugee assistance and specifically to young children's learning? And which advantages can assemblage thinking and situated knowledges bring about in analysing, understanding and transforming long-term refugee camps? Responding to the extreme lack of information about East African camps, Nerea Amorós Elorduy has built contextualised knowledge - nuanced, situated and participatory - to describe, study and transform the East African long-term camps, and uncover hidden agencies in refugee assistance. She uses architecture as a means to create new knowledge collectively, include more local voices and speculate on how to improve the educational landscape for young children. With this book, Amorós Elorduy brings nuance, contextualisation and empathy to the study and management of long-term refugee camps in East Africa. It is empathy, she argues, that will help change mindsets, decolonise humanitarian refugee assistance and its study. Crossing architecture, humanitarian aid and early career development, this book offers many practical learnings.